(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
This study consolidated our understanding on the weeds of Bhadrak district, Odisha, India based on both bibliographic sources and field studies. A total of 277species of weed taxa belonging to 198 genera and 65 families are reported from the study area. About 95.7% of these weed taxa are distributed across six major superorders; the Lamids and Malvids constitute 43.3% with 60 species each, followed by Commenilids (56 species), Fabids (48 species), Companulids (23 species) and Monocots (18 species). Asteraceae, Poaceae, and Fabaceae are best represented. Forbs are the most represented (50.5%), followed by shrubs (15.2%), climber (11.2%), grasses (10.8%), sedges (6.5%) and legumes (5.8%). Annuals comprised about 57.5% and the remaining are perennials. As per Raunkiaer classification, the therophytes is the most dominant class with 135 plant species (48.7%).The use of weed for different purposes as indicated by local people is also discussed. This study provides a comprehensive and updated checklist of the weed speciesof Bhadrak district which will serve as a tool for conservation of the local biodiversity. Bangladesh J. Plant Taxon. 27(1): 85-101, 2020 (June)